Evaluation of commercial cellulolytic enzymes for sugarcane bagasse hydrolysis - Aguiar, Mario M.; Pietrobon, Vivian C.; De Salles Pupo, Marilia Moura; Torres, Nádia Hortense; Américo, Juliana H.P. [UNESP]; Salazar-Banda, Giancarlo Richard; Silva, Daniel P.; Monteiro, Regina Teresa Rosim; Romanholo Ferreira, Luiz F. (My University, 2018)
Conversion of plant biomass to glucose requires the synergistic effort of cellulolytic enzymes. Commercial cellulolytic enzymes (HPL, CL, P1 and P4) were used for enzymatic hydrolysis of sugarcane bagasse and the amount of total released sugars was quantified. Total cellulolytic activity and the required enzyme concentration were determined. Then, the enzymes were tested with regard to their efficiency in pretreating sugarcane bagasse in acidic and alkaline solutions, followed by a steam autoclave treatment. Upon total sugars quantification, it was possible to conclude that the most efficient bagasse treatment was an acidic pretreatment procedure with commercial enzyme P4.
Keywords: Bagasse; Biomass; Cellulases; Cellulose; Total sugars